Enhancing RESTful API Authentication with Cryptography in Student Information Systems - Sucipto, Sucipto; Muzaki, Muhammad Najibulloh; Karaman, Jamilah; Zakur, Yahya (ILKOM Jurnal Ilmiah, 2024)
Data integration in this era is necessary for building a valid information system. Data in an information system must have a concept that interacts with other systems. With the development of information systems, data storage will increase. Big data must be channeled with a supporting information system connected to the data center information system. This research develops an API-integrated system with increased security in Basic Authentication with Cryptography. This research uses the Linear Sequential Model method with increased API security in Basic Authentication with Cryptographic hashes. test results using the CURL Library obtained appropriate data, and response time testing obtained an average result of 0.0611 per second. Acceptance testing obtained a percentage of results of 78%, which was included in the excellent functioning category. The research found that the Rest API can integrate and validate data between information systems